Life Cycle Cost Analysis (LCCA) for Sustainable Construction Projects: BIM Application - Abdelaziz, Abdelaziz Abdelmahmoud (Universiti Teknologi PETRONAS, 2020)
The purpose of this research is to highlight the influence of life cycle cost analysis (LCCA) in optimizing the cost for different alternatives of materials. LCCA describes and defines the whole cycle of any project form planning until demolition. LCCA is considered as an important technique that is used to evaluate and compare between different alternatives of materials. The total cost of the materials is analyzed and estimated considering the direct and indirect cost for the whole life. LCCA considers the comparison of the materials. There are several methods that can be used to evaluate the LCCA which are explained in this report. This research shows the LCCA of a central air conditioning system that is installed in block 11 in Universiti Teknologi PETRONAS (UTP). A comparison is made between an installation of the central air conditioning system with some insulation materials that help to reduce the cost of the operation and the other part of the analysis without the insulation materials. This research is analyzed in terms of the total cost, and a conclusion is made about the most effective option.